THE MOBILITY BETWEEN LANGUAGES AND THE FLUXES OF GLOBALIZATION: REVIEWING PARADIGMS, TRANSCENDING PARADOXES - Storto, André Coutinho; Biondo, Fabiana Poças (Revista da Anpoll, 2016)
This article aims to raise some general questions related to mobility and the traffic between languages in times of globalization. While defining “globalization” as a set of discourses, we outline some of its internal contradictions and paradoxes as well as the equally contradictory role of the English language as a homogenizing and fragmentary force in this context. Next, taking the perspective of language as socio discursive practice, we situate the multilingual speaker and the interweaving between languages and meanings in a world dominated by intense patterns of diversity and fluxes of people and discourses. Finally, we turn to the context of the bi/multilingual classroom, trying to point out alternatives to monolingual assumptions underlying educational and pedagogical discourses and practices related to bi/multilingual education that prevent us from understanding multilingual speakers in all their complexity. This work is licensed under a Creative Commons Attribution 3.0 License.